Simultaneous determination of tolperisone and lidocaine by high performance liquid chromatography - Liawruangrath S. (2014)
A reversed phase high performance liquid chromatographic (RP-HPLC) method for the simultaneous determination of tolperisone (TP) and lidocaine (LD) has been developed. The drugs were separated on a column (4.60 × 250 mm2) Spherisorb ODS (5 μm) using 5.5% triethylamine in 70/30 v/v acetonitrile/water as mobile phase 0.7 ml min -1and UV detection at 254 nm. The detection limits for Tolperisone hydrochloride (TP·HCl) and lidocaine hydrochloride (LD·HCl) were 0.20 ng/20 μl and 100 ng/20 μl and the quantitation limits were 0.50 ng/20 μl and 250 ng/20 μl, respectively. Linear calibration curves over the ranges of 1-10, 10-100 and 150-500 μg ml-1 for TP·HCl and 10-500 μg ml-1 for LD·HCl were established. Different calibration slopes were found for TP probably owing to changes in refractive index due to increase in TP concentration. The average recoveries of the added TP in the samples (TP·HCl tablets and injection liquid). A solutions spiked with standard TP·HCl were 99.9 and 99.7% with the RSD (n = 11) of 0.66 and 0.67%, respectively. The average recovery of the added LD in the sample (injection) spiked with standard LD·HCl was 98.9% with the RSD (n = 11) of 0.59%. The proposed method has been applied to the determination of TP·HCl and LD·HCl in commercial products available in Thailand. Comparative determination of TP by UV spectrophotometry and LD by colorimetry were also carried out. The results obtained by both methods were in good agreement of those obtained by the proposed method verified by using t-test. The proposed RP-HPLC method is simple, accurate, reproducible and suitable for routine analysis. © 2001 Elsevier Science B.V. All rights reserved.